Bagmen : a Victor Carl novel - Lashner, William (Thomas, Mercer, 2014)
Victor Carl is back, and back in trouble. At a low point in his lowly career, Victor finds himself skulking through the streets of Philadelphia carrying a bag full of money for an ambitious politician. It is a rotten job on the wrong side of anyone's line, but with bag in hand Victor is suddenly hobnobbing with the city's elite, filling his bank account, and having sex with the politician's gorgeous and deranged sister. But just when Victor begins to think he's got a future in the political game, one of his payoffs ends up in the pocket of a dead woman, and Victor goes from bagman to fall guy. Now Victor's only way out might lie with a brotherhood of shady characters with sacks full of cash, bad fedoras, and their own twisted set of rules. Will Victor's new friends help him find a killer or bury him deep?